2018
DOI: 10.1007/s00464-018-6443-2
|View full text |Cite
|
Sign up to set email alerts
|

Ileal interposition coupled with duodenal diverted sleeve gastrectomy versus standard medical treatment in type 2 diabetes mellitus obese patients: long-term results of a case–control study

Abstract: II-DD-SG is an effective surgical procedure, able to induce complete and prolonged remission of T2DM in obese patients as opposed to medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In comparison with best medical treatment, BMS is able to induce a remission of clinically overt diabetes [110], together with the improvement of cardiovascular performance (obstructive sleep apnea, left ventricular hypertrophy, hypertension, markers of early atherosclerosis), kidney function, liver function, endothelial dysfunction, and inflammation [111,112].…”
Section: Available Means To Prevent the Progression Of Prediabetes To...mentioning
confidence: 99%
“…In comparison with best medical treatment, BMS is able to induce a remission of clinically overt diabetes [110], together with the improvement of cardiovascular performance (obstructive sleep apnea, left ventricular hypertrophy, hypertension, markers of early atherosclerosis), kidney function, liver function, endothelial dysfunction, and inflammation [111,112].…”
Section: Available Means To Prevent the Progression Of Prediabetes To...mentioning
confidence: 99%
“…Folschi et al, comparing SGDII to medical treatment in T2D obese patients (BMI > 30), found, after ve years, remission in 68% of the cases. [29] Considering the duration of diabetes, more than four years, and the BMI, the rate of T2D remission after SGDII is higher than after RYGB (29%) with a ve year follow up [30] Parikh et al, on a systematic review with meta-analysis of diabetes remission among patients with a BMI < 35 kg/m 2 , found an overall rate of diabetes remission at 12 months of 54.7% of the cases, the highest one after ileal interposition (80.5% − 95% CI, 59.4-92.3%) [31] The average BMI preoperatively was 33.43 kg/m 2 , and postoperatively it was 26.17 kg/m 2 , demonstrating that surgery does not promote excessive weight loss in non-obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of IT have been performed in rats for over 30 years (20). In recent years, IT has also been used in patients, with satisfactory outcomes (21)(22)(23). Unlike RYGB and VSG, IT does not involve gastrectomy; i.e., it is a "pure" intestinal operation which is suitable for GI research.…”
Section: Discussionmentioning
confidence: 99%